Thermophysical properties of R143a (1,1,1-trifluoroethane) - Fröba, Andreas Paul; Will, Stefan; Leipertz, Alfred (International Journal of Refrigeration-Revue Internationale Du Froid, 2001)
Various thermophysical properties of refrigerant R143a (1,1,1-trifluoroethane) have been determined under saturation conditions using dynamic light scattering (DLS). Light scattering from bulk fluids was applied for measuring the thermal diffusivity and the sound velocity for both the saturated liquid and vapor phase over a wide temperature range of 273-346 K. The results were also used to obtain information on the specific heat at constant pressure and the isentropic compressibility. Furthermore, the surface tension and liquid kinematic viscosity were determined simultaneously in the temperature range 253-333 K from light scattering by surface waves on a horizontal liquid-vapor interface. All experiments are based on a heterodyne detection scheme and a signal analysis by photon correlation spectroscopy (PCS). The results for R143a are discussed in detail and compared to literature data available. (C) 2001 Elsevier Science Ltd and IIR. All rights reserved.
Keywords: refrigerant; R143a; physical property; thermodynamic property; measurement